The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.5194/bg-9-5007-2012
|View full text |Cite
|
Sign up to set email alerts
|

Nitrous oxide dynamics in low oxygen regions of the Pacific: insights from the MEMENTO database

Abstract: Abstract. The eastern tropical Pacific (ETP) is believed to be one of the largest marine sources of the greenhouse gas nitrous oxide (N 2 O). Future N 2 O emissions from the ETP are highly uncertain because oxygen minimum zones are expected to expand, affecting both regional production and consumption of N 2 O. Here we assess three primary uncertainties in how N 2 O may respond to changing O 2 levels: (1) the relationship between N 2 O production and O 2 (is it linear or exponential at low O 2 concentrations?)… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
54
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(60 citation statements)
references
References 79 publications
6
54
0
Order By: Relevance
“…This is in line with the results of two model studies of N 2 O in the ETSP by Zamora et al (2012) and Cornejo and Farias (2012), which suggested that the switching point between N 2 O production and N 2 O consumption occurs at higher O 2 concentration (∼ 8-10 µmol kg −1 ) than previously thought.…”
Section: Nitrous Oxide (N 2 O) In Omzsupporting
confidence: 80%
See 1 more Smart Citation
“…This is in line with the results of two model studies of N 2 O in the ETSP by Zamora et al (2012) and Cornejo and Farias (2012), which suggested that the switching point between N 2 O production and N 2 O consumption occurs at higher O 2 concentration (∼ 8-10 µmol kg −1 ) than previously thought.…”
Section: Nitrous Oxide (N 2 O) In Omzsupporting
confidence: 80%
“…In general, we might expect enhanced production of N 2 O, CH 4 and DMS in OMZs because of the ongoing loss of O 2 . Deoxygenation in open-ocean and coastal environments may lead, on the one hand, to enhanced N 2 O production when approaching the N 2 O production-consumption switching point (see above), but, on the other hand, when O 2 concentrations fall below the switching point this may lead to a consumption of N 2 O (Zamora et al, 2012). Moreover, we do not know whether the frequency of coastal anoxic events will continue to increase and how this may affect the coastal net N 2 O production/consumption.…”
Section: Trace Gas Production In Omz and Environmental Changesmentioning
confidence: 99%
“…However, even N 2 O production at relatively high surface layer nitrification rates, as found in upwelling regions (Rees et al, 2011), are orders of magnitudes too low to significantly bias the large fluxes caused by deliberate N 2 O addition. The only known pathway of biological N 2 O uptake as a reactive nitrogen species is by denitrifiers at anoxic conditions (<∼ 10 µmol O 2 kg −1 ) (Zumft, 1997;Zamora et al, 2012). Conditions favouring this process are unlikely to form in mesocosms and would result in a loss of the tracer (as N 2 ) but not into utilisation of N 2 O as a nitrogen source.…”
Section: The Choice Of N 2 O As a Gas Exchange Tracer And Its Biologimentioning
confidence: 99%
“…Recently, Zamora et al (2012) suggested that N 2 O production increases linearly with decreasing oxygen, rather than exponentially, in the eastern tropical Pacific, based on MEMENTO database. This fundamental difference in N 2 O production parameterization introduces a large uncertainty in biogeochemical models, especially in EBUS and associated OMZs (Zamora et al, 2012), even more in a context of expansion and intensification of the OMZs (Stramma et al, 2008;Deutsch et al, 2010).…”
Section: E Gutknecht Et Al: Coupled Physical/biogeochemical Modelinmentioning
confidence: 99%